Rheological investigation of three South African gold mine pulps - Levy, Charles David (Department of Mechanical Engineering, 2015)
A method is described which enables the user to determine the rheological parameters of a fast settling slurry using conventional viscometric measuring equipment. The effect of concentration, temperature and pH on these parameters is investigated. The results agree with those obtained by previous workers using different viscometers. However, this method allows a more detailed characterization of all the properties. A literature survey was carried out and two semi-empirical correlations were found, which allow the effect of either concentration, temperature or pH on the rheological parameters to be investigated.